2020
DOI: 10.1177/2054358119898016
|View full text |Cite
|
Sign up to set email alerts
|

Significant Burden and Psychological Distress Among Caregivers of Children With Nephrotic Syndrome: A Cross-Sectional Study

Abstract: Background: Childhood nephrotic syndrome (NS) follows a chronic course in most children. However, little is known about the psychosocial burden of NS on the caregivers despite evidence that caregiver burden or impairment in their well-being may alter the outcome of chronic childhood illnesses. Objectives: To determine the frequency and predictors of significant caregiver burden and psychological distress among caregivers of children with NS. Design: A cross-sectional study. Setting: Two pediatric nephrology cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
7
2
Order By: Relevance
“…While a high rate of emotional distress in our study underscores the burdensome nature of caregiving in children with chronic illnesses in consonance with earlier works, the rate of caregiver distress across other chronic childhood illnesses compare to our study is mixed, albeit significant. For example, a higher proportion of caregivers of children with obstructive adenotonsillar hypertrophy (48%) relative to our study was emotionally distressed, whereas lower rates of distress were found in caregivers of children with neurodevelopmental disorders (38.3%), and nephrotic syndrome (30.8%) compared to our study (Esezobor et al, 2020; Olagunju et al, 2015, 2017). On a different note, the prevalence of emotional distress in our study participants is several folds the rates of distress reported in caregiving mothers of normal full-term children, and the general adult population in comparable settings (Erinfolami et al, 2016; Ukpong et al, 2003).…”
Section: Discussioncontrasting
confidence: 82%
“…While a high rate of emotional distress in our study underscores the burdensome nature of caregiving in children with chronic illnesses in consonance with earlier works, the rate of caregiver distress across other chronic childhood illnesses compare to our study is mixed, albeit significant. For example, a higher proportion of caregivers of children with obstructive adenotonsillar hypertrophy (48%) relative to our study was emotionally distressed, whereas lower rates of distress were found in caregivers of children with neurodevelopmental disorders (38.3%), and nephrotic syndrome (30.8%) compared to our study (Esezobor et al, 2020; Olagunju et al, 2015, 2017). On a different note, the prevalence of emotional distress in our study participants is several folds the rates of distress reported in caregiving mothers of normal full-term children, and the general adult population in comparable settings (Erinfolami et al, 2016; Ukpong et al, 2003).…”
Section: Discussioncontrasting
confidence: 82%
“…Esezobor et al found that 30.8% of caregivers suffered psychosocial distress. Chronic nature of disease, frequent hospitalization, and frequency of relapse play important role in the severity of psychosocial distress [15]. In contrast, Roussel et al found that quality of life of children with difficult-to-treat" nephrotic syndrome was still high and close to children without any chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Median age of patients with nephrotic syndrome in a study from Indonesia was 8.5 years with male predominance at a ratio of 2:1 to 3:2 [7]. A study by Esezobor et al found that median age of children with nephrotic syndrome was 7.3 years [15]. Roussel et al reported a higher mean age which was 11.6 years [2].…”
Section: Discussionmentioning
confidence: 99%
“…Such feelings may also indirectly affect the child's psychological state, which can further negatively impact on their quality of life ( 17 ). Rüth et al ( 1 ) showed that parents' (especially mothers') negative emotions severely negatively impacted the quality of life and psychological wellbeing of children with PNS, which may cause a further increase in the negative emotions of the parents, forming a vicious cycle ( 18 ). Pediatricians and nurses want to offer long-term standardized treatment to children with PNS through a comprehensive management protocol to improve their quality of life ( 19 ).…”
Section: Discussionmentioning
confidence: 99%